Endogenous T-cell receptor promotes in vivo persistence of CD19-CAR-T cells compared to a CRISPR/Cas9-mediated T-cell receptor knockout CAR - Stenger, Dana (Blood, 2020)
Anti-CD19 chimeric antigen receptor (CAR) T cells showed significant anti-leukemic activity in B-precursor acute lymphoblastic leukemia (ALL). Allogeneic, HLA-mismatched off-the-shelf 3(rd)-party donors may offer ideal fitness of the effector cells but carry the risk of graft-versus-host disease. Knockout of the endogenous T-cell receptor (TCR) in CD19-CAR-T cells may be a promising solution. Here, we induced a CRISPR/Cas9-mediated knockout of the TCRβ-chain in combination with a 2(nd)-generation retroviral CAR transduction including a 4-1BB costimulatory domain in primary T cells. This tandem engineering led to a highly functional population of TCR-KO-CAR-T cells with strong activation (CD25, IFN-γ), proliferation and specific killing upon CD19 target recognition. TCR-KO-CAR-T cells had a balanced phenotype of central memory and effector memory T cells. KO of the endogenous TCR in T cells strongly ablated alloreactivity in comparison to TCR-expressing T cells. In a patient-derived xenograft model of childhood ALL, TCR-KO-CAR-T cells clearly controlled CD19(+) leukemia burden and improved survival in vivo. However, coexpression of endogenous TCR plus CAR led to superior persistence of T cells and significantly prolonged leukemia control in vivo, confirmed by a second in vivo model using NALM6 leukemia cells. These results point towards an essential role of the endogenous TCR for longevity of the response at the price of alloreactivity. In conclusion, anti-CD19 CAR-T cells with a CRISPR/Cas9-mediated TCR-KO are promising candidates for non-matched third-party adoptive T-cell transfer with high anti-leukemic functionality in the absence of alloreactivity, but long-term persistence in vivo is better in the presence of the endogenous TCR.